Construction of Spectral Discoloration Model for Red Lead Pigment by Aging Test and Simulating Degradation Experiment. (1st September 2016) - Liang, Jinxing; Wan, Xiaoxia; Li, Chan; Li, Junfeng; Liu, Qiang; Cao, Qian
Abstract : The construction of spectral discoloration model, based on aging test and simulating degradation experiment, was proposed to detect the aging degree of red lead pigment in ancient murals and to reproduce the spectral data supporting digital restoration of the ancient murals. The degradation process of red lead pigment under the aging test conditions was revealed by X-ray diffraction, scanning electron microscopy, and spectrophotometer. The simulating degradation experiment was carried out by proportionally mixing red lead and lead dioxide with referring to the results of aging test. The experimental result indicated that the pure red lead was gradually turned into black lead dioxide, and the amount of tiny particles of the aging sample increased faced with aging process. Both the chroma and lightness of red lead pigment decreased with discoloration, and its hue essentially remains unchanged. In addition, the spectral reflectance curves of the aging samples almost started rising at about 550 nm with the inflection moving slightly from about 570 nm to 550 nm. The spectral reflectance of samples in long- and in short-wavelength regions was fitted well with the logarithmic and linear function. The spectral discoloration model was established, and the real aging red lead pigment in Dunhuang murals was measured and verified the effectiveness of the model.